Rescue of refractory splicing of cftr exon 12 pathological mutations G576A/G48C using antisense oligonucleotides - Haque, Ariful (Journal of Bio-Science, 2011)
Context: Pathological mutation in the human CFTR (Cystic Fibrosis Transmembrane conductance Regulator) exon 12 sequences disrupts splicing enhancer that leads to cystic fibrosis disease. Objectives: Human CFTR exon 12 architecturally consists of two exonic regulatory silencers (Exonic Splicing Silencer / ESS) and an enhancer (Exonic Splicing Enhancer / ESE). In this study it was aimed to block the silencer activity as well as to introduce well known enhancer sequence along with the RNA to rescue CFTR exon 12 inclusion for therapeutic purpose. Materials and Methods: In order to alter the pathologic RNA splicing event of CFTR exon 12 two oligonucleotides (ESE-A and ESS-B) were designed that, although complementary to the target RNA sequence but do not interfere in RNA processing. The oligonucleotide ESE-A additionally contains a non-complementary tail sequence mimicking ESE sequence. In this way the ESE were designed consequently for blocking silencer activity and enhance splice site selection. Furthermore, these oligonucleotides were designed based on several well known modified nucleotide sequences to provide stability from in vivo degradation. Results: Naturally occurring pathological point mutation G576A/G48C in CFTR exon 12 causes complete skipping of the exon from full transcript. This study shows that cotransfection of oligonucleotides ESS-B along with CFTR exon 12 minigene carrying G576A/G48C mutation can rescue exon skipping. Conclusion: The use of oligonucleotide ESS-B to enhance expression of latent CFTR exon 12 may ultimately be of therapeutic use for cystic fibrosis patient carrying pathological mutation in CFTR exon 12. Keywords: CFTR exon 12; RNA splicing; Antisense Oligonucleotides. DOI: http://dx.doi.org/10.3329/jbs.v18i0.8771 JBS 2010; 18(0): 27-33